Pengaruh Budaya Madrasah Terhadap Kinerja Guru di Madrasah Ibtidaiyah (MI) Ma’arif NU 1 Karanggambas Kecamatan Padamara Kabupaten Purbalingga - Siti Honiah Mujiati (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2020)
This research is based on the problem of unsatisfactory teacher performance. In this regard, this study aims to determine the effect of madrasa culture and the madrasa environment on teacher performance at MI Ma'arif NU 1 Karanggambas, Padamara District, Purbalingga Regency. This research is a quantitative research. The population and sample in this study were all teachers at MI Ma'arif NU 1 Karanggambas, Padamara District, Purbalingga Regency, totaling 12 people. Data collection used a questionnaire, and data analysis used simple regression and multiple regression analysis techniques. This study resulted in the conclusion that Madrasah Culture has a significant influence on Teacher Performance MI Ma'arif NU 1 Karanggambas, Padamara District, Purbalingga Regency, as evidenced by the value of Sig = 0.01 < α = 0.05. The value of the correlation coefficient (r2) = 0.503 or a contribution of 50.3%.